Perceptions of the MDT towards the health needs and support for grandparents caring for AIDS orphans - Furaha Akimanimpaye; Million S. Bimerew; Isaiah D. Owoeye; Deliwe R. Phetlhu (AOSIS, 2024)
Background: The acquired immunodeficiency syndrome (AIDS) crisis has orphaned many children, shifting care giving duties to grandparents. This has challenged the health of the grandparents, underscoring the need for support in caring for both the grandparents and the children orphaned due to AIDS. Aim: This study investigated the multidisciplinary team's (MDT) perceptions of health needs and support for grandparents caring for children orphaned due to AIDS. Setting: The study took place within Metropolitan area in the Western Cape Province, South Africa. Methods: A cross-sectional descriptive survey was used to assess health needs and support for grandparents caring for children orphaned due of AIDS. A sample of 65 MDT members comprising professional nurses, psychologists and social workers participated in the study. Results: The assessment revealed moderate awareness (mean 2.79) among MDT regarding the health needs of grandparents caring for the orphans. Key concerns were a lack of income (mean = 4.9) and no access to health services (mean = 4.8), with low awareness and involvement in organisational support (mean = 1.8). Conclusion: Despite an awareness of the health needs and support perceptions among grandparents, there remains a significant gap in the availability of support structures to address these needs. The study highlights the critical necessity for developing robust support systems to enhance the well-being of grandparents, especially those caring for AIDS orphans, ensuring they receive the comprehensive care and assistance required. Contribution: The study's findings provide key insights for supporting grandparents who are caring for AIDS orphans via a MDT approach.